Anton Steen, Between Past and Future: Elites, Democracy and the State in Post Countries: A Comparison of Estonia, Latvia and Lithuania, 1997, Aldershot: Ashgate, 389 + XX s., £47.50. - Johannsen, Lars (Politica, 1998)
-